The effect of progressive drought on water relations and photosynthetic performance of two grapevine cultivars (Vitis vinifera L.) - Zsófi, Zsolt (Acta Biologica Szegediensis, 2008)
Preliminary measurements were carried out in order to asses the effect of water deficit on photosynthesis and water relations of two grapevine cultivars (Vitis vinifera L. cv. Kékfrankos and Vitis vinifera L. cv. Portugieser grafted on 5BB rootstock) tolerance and sensitive to drought, respectively. Three treatments were applied on both cultivars such as 100%, 50% and 30% field capacity under glasshouse conditions. Pre-dawn water potential and gas-exchange parameters (assimilation rate, transpiration, stomatal conductance) were consistently lower in drought stressed plants indicating moderate water stress at 50% field capacity and severe water deficit at 30% field capacity. Midday water potential indicated “close to isohydric” characteristic of both cultivars. Moderate water deficit resulted in an increase in water-use efficiency (WUE). However, Kékfrankos had a significantly higher WUE than Portugieser.